Familial dietary intervention in children with excess body weight and its impact on eating habits, anthropometric and biochemical parameters - Strączek, Kamilla; Horodnicka-Józwa, Anita; Szmit-Domagalska, Justyna; Jackowski, Tomasz; Safranow, Krzysztof; Petriczko, Elżbieta; Walczak, Mieczysław (Frontiers in Endocrinology, 2022)
Introduction Obesity is considered a civilisation disease which increases mortality and impairs quality of life, also among children and adolescents. The prevalence of overweight and obesity is steadily increasing in the developmental age population. Environmental factors are responsible for the main reason of excessive adipose tissue accumulation. Among these, poor eating habits and lack of exercise play the largest role. Familial prevalence of obesity and family dietary patterns also receive significant attention. Many specialists believe that the treatment of obesity should be multidirectional, effective and minimally invasive. Therefore, effective and safe methods are being investigated to effectively reduce body weight and improve eating habits. Dietary education programmes are an alternative to improve the health status of obese and overweight children and adolescents. To be fully effective, these programmes should involve the whole family. Aim of the study In the face of constantly increasing prevalence of overweight and obesity in the developmental age population and the lack of effective methods to combat its occurrence, it seems appropriate to try to assess the effectiveness of a one-year-long dietary education of children and adolescents with excess body weight on their eating habits and the eating habits of their mothers, as well as selected anthropometric and biochemical parameters in these children using a simple educational tool, the Healthy Food Pyramid. Patients and methods The study group consisted of 68 children with overweight and obesity, patients of the Department of Paediatrics, Endocrinology, Diabetology, Metabolic Diseases and Cardiology of the Developmental Age of the Pomeranian Medical University in Szczecin. The study used a proprietary questionnaire to assess dietary habits. Patients participated in six individual educational meetings over a twelve-month period. Eating habits were assessed in children and mothers before and after dietary intervention. Sixty-seven questionnaires before and after the dietary intervention were used for analysis. Results Sixty-eight children completed the study. Those who did not complete the study came from families living in rural areas and their mothers mostly had primary or vocational education. One-year dietary education resulted in significant improvements in body weight, waist and hip circumference, WHtR and selected measured carbohydrate and lipid metabolism parameters with the exception of total cholesterol. The one-year dietary intervention did not have the same effect on the change in dietary habits in children and in their mothers.